2006
DOI: 10.1007/s00247-006-0248-5
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and postnatal imaging of a girl with a cloacal variant

Abstract: We describe the prenatal MR findings in a 29-week fetus with a cloacal variant (urogenital sinus and anterior placed anus) in combination with an enlarged clitoris and urethral duplication and correlate them with postnatal imaging. Fetal MR imaging permits the diagnosis and characterization of cloacal and urogenital sinus malformations in utero. This information may guide pre-, peri-and postnatal management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…In this series, the associated incidence for posterior cloacas was 93%. The most frequent urologic malformation found in posterior cloacas was an accessory urethra that has also been described by other authors [8,9,13]. As already mentioned, it is a very stenotic urethra; and its reconstruction should not be attempted because the patient has a functioning urethra that is posteriorly deviated.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In this series, the associated incidence for posterior cloacas was 93%. The most frequent urologic malformation found in posterior cloacas was an accessory urethra that has also been described by other authors [8,9,13]. As already mentioned, it is a very stenotic urethra; and its reconstruction should not be attempted because the patient has a functioning urethra that is posteriorly deviated.…”
Section: Discussionsupporting
confidence: 55%
“…In our literature review, we found authors referring to this defect as posterior cloaca [2,3,7-9]; but we also found terms such as partial urorectal septal defect and others [10][11][12][13][14] in which the anatomical features, seen in photographs and diagrams, were consistent with the diagnosis of a posterior cloaca.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, fetal MRI is progressively used for the evaluation of the fetal thorax and abdomen. Fetal MRI serves as a complementary imaging tool to prenatal US; it is especially advantageous compared to prenatal US because of its high spatial resolution, the high T 2 contrast between fluid and solid tissue, the large field of view and that imaging is not obscured by maternal bowel gas, maternal obesity or overlying pelvic bony structures [7] . In particular, fetal MRI provides reliable information concerning the survey of the internal organs including the CNS, detecting associated anomalies or abnormal brain maturation, and allows to analyze lung development and functionality using fetal lung volume measurements [25,26] and the MR signal characteristics of the lungs [27,28] .…”
Section: Discussionmentioning
confidence: 99%
“…because of its high spatial and soft tissue resolution, the high T 2 contrast between fluid and solid tissue, the large field of view and the absence of obscuring maternal bowel gas or pelvic bony structure artifacts [7] . During the last decade, molecular diagnosis including structure analysis of collagen molecules in cultured fibroblasts obtained from chorion villus sampling and amniocytes as well as genomic DNA screening has become an useful tool in the diagnostic work-up of suspected skeletal dysplasia.…”
mentioning
confidence: 99%
“…The lack of anal opening confirms the cloacal anomaly when associated with pelvic lesion. Infrequently, ambiguous genitalia are seen and the diagnosis could be difficult [4] . In cloacal malformations, a penis-like structure could be seen, but with 3-D ultrasonography, the diagnosis could be an enlarged wrinkled clitoral-like structure.…”
mentioning
confidence: 99%